1985
DOI: 10.1093/jnci/75.5.841
|View full text |Cite
|
Sign up to set email alerts
|

A Monoclonal Antibody Against γ-Glutamyltransferase From Human Primary Hepatoma: Its Use in Enzyme-Linked Immunosorbent Assay of Sera of Cancer Patients2

Abstract: A monoclonal antibody, gamma-120, was raised against a highly purified gamma-glutamyltransferase (gamma GT) from human primary hepatoma. The antibody preferentially bound to the small subunit of gamma GT from human hepatoma and kidney as evidenced by immunoblot analysis. Weak binding to the normal liver enzyme could be detected by solid-phase enzyme-linked immunosorbent assay (ELISA). With the use of this antibody, an ELISA was developed for the quantitation of immunoreactive gamma GT in human serum. Sera of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Although several anti-GGT monoclonal antibodies have been described that reacted with tissues of normal human kidney [4,22], or hepatocellular carcinoma [26], our mAb 138Hll is the only of these mAbs that proved to be specifically reactive with GGT from human renal cell carcinomas [8].…”
Section: Discussionmentioning
confidence: 78%
“…Although several anti-GGT monoclonal antibodies have been described that reacted with tissues of normal human kidney [4,22], or hepatocellular carcinoma [26], our mAb 138Hll is the only of these mAbs that proved to be specifically reactive with GGT from human renal cell carcinomas [8].…”
Section: Discussionmentioning
confidence: 78%
“…5A), and the resulting chimeric protein was expressed in COS cells. As revealed by immunofluorescence microscopic analysis using anti-GGT antibody (30), the insertion of the domain had a dramatic effect on the localization of the protein: the chimeric protein was localized in the intracellular organelles, predominantly the Golgi apparatus, in contrast to the cell surface expression of the nonchimeric GGT (Fig. 5B).…”
Section: Resultsmentioning
confidence: 99%
“…Expression of GGT is elevated in hepatic diseases and chronic alcoholism (33,36,37), which are frequently accompanied with osteopenia and osteoporosis (38,39). Recently, it has been reported that OPG prevents an ethanol-mediated bone loss by inhibiting osteoclast formation (40).…”
Section: Discussionmentioning
confidence: 99%